Zastosowanie metody różnic skończonych do zagadnień pełzania kołowo cylindrycznych powłok - Sumio Marakami (Engineering Transactions)
The numerical approach to creep deformation in pressurized circular cylindrical shells is developed by way of the finite difference method, and some features of the deformation in the shells are elucidated. In Part I of the paper, the transient creep analysis of circular cylindrical shell is developed on the basis of the power creep law and the creep theories of Mises-Mises, Tresca-Mises and Tresca-Tresca type. Use is made of the strain-hardening hypotheses. The creep deformation and the associated state of stress is investigated for various shell geometries and various magnitudes of internal pressure. The difference between the creep theories and hardening hypotheses as applied to the present problem is also discussed. Calculations are performed for constant as well as variable internal pressures. Part II is concerned with the analysis of the steady-state crcep of a circular cylindrical shell according to the power creep law nad the creep theory of Mises-Mises type. An iterative procedure combined with the finite-difference method is proposed. The effect of shell geometry and the creep exponent on the state of stress and rate of deformation is investigated. The rigorous results obtained are also compared with the previous solution on the basis of a sandwich shell, and the validity of the assumption of sandwich construction is discussed.